Effect of bra type on body armour comfort and fit - raw data - Malbon, Christopher (Cranfield University, 2021)
Bra type and sizing of female police officers from England and Wales. Including 3D body scanning measurements in relation to the upper torso. Survey results of pre and post wearing of a cohort of female police officers in recently fitted underwired and sports bras.
Keywords: 'anthropometric measures'; 'bra type'; 'body armour'; 'Materials Engineering not elsewhere classified'